Mobile cloud computing on Android phone - Toh, Han Keong. (2012)
With the prevalence of wireless network and smartphone becoming more and more sophisticated. As a result, developers are writing complex application that needs huge amounts of computation power and energy. In this project we will focus on the performance of offload on android phone.